2017
DOI: 10.1111/jcmm.13317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of collagen peptides intake on skin ageing and platelet release in chronologically aged mice revealed by cytokine array analysis

Abstract: Action mechanisms underlying various biological activities of collagen peptides (CPs) remained to be elucidated. Cytokines may play an important role in mediating these health benefits of CPs. This study aimed to systemically examine the cytokines in skin and blood regulated by CPs intake. Thirteen‐month‐old female Kunming mice were administered with CPs for 2 months (0 or 400 mg/kg bodyweight/day). The cytokines in skin and plasma were analysed using a 53‐cytokine array and corresponding ELISA kits. In skin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…Due to the high turnover of the platelet in the body and its essential role in hemostasis and thrombosis, the platelet has long been a primary target for therapeutic intervention for the prevention of occlusive thrombotic events (Yeung et al, 2018). Our previous study has shown that oral administration of collagen hydrolysates significantly downregulated nine cytokines that are highly expressed in elder mice platelets to inhibit their activation (Song et al., 2018). However, the peptide sequence with antiplatelet aggregation activity remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high turnover of the platelet in the body and its essential role in hemostasis and thrombosis, the platelet has long been a primary target for therapeutic intervention for the prevention of occlusive thrombotic events (Yeung et al, 2018). Our previous study has shown that oral administration of collagen hydrolysates significantly downregulated nine cytokines that are highly expressed in elder mice platelets to inhibit their activation (Song et al., 2018). However, the peptide sequence with antiplatelet aggregation activity remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, most of these studies have focused on the function evaluation and there is scanty report on the sequence of collagen peptides as well as their molecular regulatory mechanisms. Our previous study has shown that oral administration of collagen hydrolysates could downregulate nine cytokines significantly, which were highly expressed in activated platelet (Song, Zhang, Luo, Zhang, & Li, 2018). However, the peptide sequence and the anti‐thrombotic effects in vivo and the mechanism remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen peptides (CPs) have been widely reported to exert beneficial effects on photoaging skin, but few studies was carried out to evaluate their effect on chronologically aged skin. In present study, 13-month-old Kunming mice, equivalent to 45 years old of human life [ 29 ], were employed to investigate the effect of CPs on chronologically aged skin. In several previous clinical trials, a daily dose of 2.5 g or 5 g of CPs has been employed in adult subjects, and these doses were considered to be safe [ 16 , 17 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chicken combs and wattles were ground and homogenized at the ratio of 1:1 (w/w). This The oral ingestion of collagen peptides has been correlated with decreasing levels of platelet release indicators in plasma and increasing levels of type I collagen, which, in turn, improves aged skin collagen fibers [26]. This was particularly attributed to an enrichment of Pro-Hyp derived from Gly-Pro-Hyp hydrolysis, which was deposited in the skin [27].…”
Section: Optimization Of Hydrolysis Of Extracts From the Chicken Combmentioning
confidence: 98%